Neutrophil-to-lymphocyte ratio and systemic inflammation response index as biomarkers for the clinical outcomes of intracerebral hemorrhagic stroke patients: a prospective cohort study - Ziyi Hu; Wei Zhu; Chaofeng Fan; Yan Jiang (Frontiers in Neurology)
PurposeTo examine the associations between the neutrophil-to-lymphocyte ratio (NLR), systemic inflammation response index (SIRI) and clinical outcomes of intracerebral hemorrhagic (ICH) stroke patients.MethodsThis prospective cohort study recruited and investigated longitudinally 294 ICH stroke patients in a general tertiary hospital in Sichuan Province, China at baseline (admission), 1-month post-discharge, 3-month post-discharge and 6-month post-discharge from January 2020 to January 2022. We calculated the NLR and SIRI from blood samples collected at baseline. The Mann–Whitney test, logistic regression analysis and receiver operating characteristic (ROC) analysis were performed to evaluate differences in the NLR and SIRI between hemorrhagic stroke patients at three follow-up time points. The interaction between these variables was evaluated via multiplicative and additive interaction models.ResultsOur study revealed that the cut-off values of the NLR and SIRI to predict the clinical outcomes were determined to be 6 and 4, respectively. NLR > 6 (OR 2.202, 95% CI: 1.094–4.430) and SIRI>4 (OR 2.056, 95% CI: 1.065–3.968) were associated with increased risks for poor clinical outcomes at 1-month post-discharge. SIRI>4 (OR 2.428, 95% CI: 1.389–4.243) were associated with increased risks for poor clinical outcomes at 3-month post-discharge. NLR > 6 (OR 1.978, 95% CI: 1.093–3.580) were associated with increased risks for poor clinical outcomes at 6-month post-discharge.ConclusionThe NLR and SIRI did not have an additive effect on the clinical outcome at 1-month post-discharge. Our findings indicate that high NLRs and SIRIs, particularly NLR > 6 and SIRI>4, are associated with poor clinical outcomes in ICH stroke patients.